Diseño de una guía metodológica para la implementación de un biodigestor para la generación de energía térmica. (2021)
This project is developed to evaluate the technical and economic viability of the production of thermal energy, thus designing a methodological guide for the implementation of a biodigester based on bovine excrement in the El Destino farm, in order to find alternatives for the high costs of electricity. Because its economic activity is the production of milk, its necessary to wash and disinfect the milking equipment rigorously with hot water, for this, the implementation of a biodigester that produces biogas is analyzed and, with the thermal energy obtained from it, boiling water and thus clean the equipment.